Clinical audit in veterinary practice: theory v reality - Waine, Katie; Brennan, Marnie L. (BMJ Publishing Group, 2015)
CLINICAL AUDIT is an effective tool for assessing and improving the clinical care provided to patients. Good guidance has previously been provided in the veterinary literature as to how to conduct clinical audit in veterinary practice (Mosedale 1998, Viner 2009, 2010, 2012, Dunn 2012, RCVS Knowledge 2015). These resources go into depth about how to conduct audit and the types of topics to choose. However, the combination of the limited veterinary evidence-base and the reality of practice makes traditional clinical audit as per the framework derived from the medical field challenging to implement in the veterinary setting. Despite this, it can still be a rewarding and valuable tool to use in practice.